Bone resorption by osteoclasts involves fine tuning of RHOA activity by its microtubule-associated exchange factor GEF-H1 - Morel, Anne; Douat, Christophe; Blangy, Anne; Vives, Virginie (Frontiers in Physiology, 2024)
Bone health is controlled by the balance between bone formation by osteoblasts and degradation by osteoclasts. A disequilibrium in favor of bone resorption leads to osteolytic diseases characterized by decreased bone density. Osteoclastic resorption is dependent on the assembly of an adhesion structure: the actin ring, also called podosome belt or sealing zone, which is composed of a unique patterning of podosomes stabilized by microtubules. A better understanding of the molecular mechanisms regulating the crosstalk between actin cytoskeleton and microtubules network is key to find new treatments to inhibit bone resorption. Evidence points to the importance of the fine tuning of the activity of the small GTPase RHOA for the formation and maintenance of the actin ring, but the underlying mechanism is not known. We report here that actin ring disorganization upon microtubule depolymerization is mediated by the activation of the RHOA-ROCK signaling pathway. We next show the involvement of GEF-H1, one of RHOA guanine exchange factor highly expressed in osteoclasts, which has the particularity of being negatively regulated by sequestration on microtubules. Using a GEF-H1 knock-down osteoclast model, we demonstrated that RHOA activation upon microtubules depolymerization is mediated by GEF-H1 release. Interestingly, although lower levels of GEF-H1 did not impact sealing zone formation in the presence of an intact microtubule network, sealing zone was smaller leading to impaired resorption. Altogether, these results suggest that a fine tuning of GEF-H1 through its association with microtubules, and consequently of RHOA activity, is essential for osteoclast sealing zone stability and resorption function.